Optimalisasi Kompetensi Relegius Siswa Tunagrahita : Melalui Pendekatan Demonstrasi dan Drill di SLB Insan Mulia Payakumbuh - Musdeli Yani; Rizki Pebrina (SURAU : Journal of Islamic Education, 2025)
This study examines cognitive challenges experienced by students with intellectual disabilities that affect memory retention and generalization in performing religious practices, particularly shalat. Although demonstration and drill methods have been implemented at SLB Insan Mulia Payakumbuh, instructional approaches are not always aligned with students’ limited attention and comprehension abilities. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation. The findings indicate that learning effectiveness is largely influenced by adaptive teaching strategies, including task-analysis-based instructional modules, the use of concrete learning media, and continuous individualized guidance. While limitations in short-term memory and variations in intellectual abilities remain significant challenges, consistent prompting combined with positive reinforcement has proven effective in improving students’ independence in performing religious practices according to their cognitive capacities.